Wireless Sensor Network for Landslide Monitoring in Nusa Tenggara Timur - Herry Z. Kotta; Kalvein Rantelobo; Silvester Tena; Gregorius Klau (Universitas Ahmad Dahlan, 2011)
Landslides in many regions constitute serious hazards that cause substantial life and financial losses. To overcome and reduce the damages, efforts to monitor landslides are developed. One such technology utilizes a wireless sensor network (WSN). Results obtained from studies conducted in the Ikanfoti village, Kupang District, Nusa Tenggara Timur (NTT) Province (S 10o16’ 21.9” and E 123o40’59.8”) as pilot project, give result that the application of WSN can be applied properly. We detect and measure vibrations caused by landslides by vibration sensor (accelerometer) on Micaz devices. The results of this study indicate that changes in accelerometer values ranging from 0.2 g (gravity) to 0.49 g of either the X or Y of accelerometer indicate that soil begins to move but not significantly. Value above 0.5 g is a value that indicating a significant change of ground motion. The value of 1 g and above of ground motion indicates a very strong activity and should be alarmed. It is expected that this research provides the foundation for the application of WSN in various areas in NTT Province and Indonesia in general, for establishing thorough and reliable early warning system (EWS).